PROBLEMS OF WEAR OF THE CHAINS USED IN MINE SCRAPER CONVEYORS, CAUSED BY FRICTION AND CORROSION - Andrzej Norbert WIECZOREK; Mateusz WÓJCICKI; Marek KALITA; Richard KANDZIA (Scientific Journal of Silesian University of Technology. Series Transport)
Scraper chains are the main transport cables of scraper conveyors. Problems related to the processes of destruction of link chains used in these conveyors are described. Design of scraper chains and their division into different types for use in scraper conveyors are presented. The most common damages to chains used in scraper conveyors are presented and the reasons of their wear are discussed.